Ordinary ethics : anthropology, language, and action. - Lambek, Michael (Fordham University Press, 2010)
What is the place of the ethical in human life? How do we render it visible? How might sustained attention to the ethical transform anthropological theory and enrich our understanding of thought, speech, and social action? This volume offers a significant attempt to address these questions. It is a common experience of most ethnographers that the people we encounter are trying to do what they consider right or good, are being evaluated according to criteria of what is right and good, or are in some debate about what constitutes the human good. Yet anthropological theory has tended to overlook all this in favor of analyses that emphasize structure, power, and interest.